Changes in work characteristics over 12 years: Findings from the 2002‐2014 US National NIOSH Quality of Work Life Surveys. Issue 6 (2nd May 2019) - Myers, Stephanie; Govindarajulu, Usha; Joseph, Michael; Landsbergis, Paul
Abstract: Objectives: To assess changes in work characteristics, socioeconomic status inequalities in changes in work characteristics, and whether US workplaces are becoming more stressful. Methods: We analyzed data from 5361 employed participants from the 2002, 2006, 2010, and 2014 NIOSH Quality of Work Life Surveys, based on representative samples of US workers. We used regression analyses to assess changes in job characteristics, adjusting for age, sex, race/ethnicity, education, work hours, and unemployment rate. For the regression analyses with continuous job characteristics, we created standardized variables allowing for the magnitude of changes to be directly compared between job characteristics. Results: Over the period 2002‐2014, we observed statistically significant increases in job strain (+0.09 standard deviations (SD), P  = 0.02), low job control (+0.10 SD, P  = 0.03), and work‐family conflict (+0.15 SD, P  = 0.001). No significant changes were observed for high job demand, low social support, and low reward. The largest increase in low job control was seen among service workers. Conclusions: The increase in two cardiovascular disease risk factors, job strain, and low job control, might partially explain the slowing of the decline in US heart disease and stroke mortality rates.